Effect of process parameters on the temperature changes during robotic bone drilling. (August 2022) - Han, Ying; Cai, Chenxu; Lv, Qinjing; Song, Yixuan; Zhang, Qinhe
In medical surgery, bone drilling is an inevitable procedure. The thermal necrosis in the drilling process can affect post-operative recovery. In this study, the method of drill bit precooling is proposed in bone drilling with robot assisted system. The influence of process parameters on the drilling temperature were investigated and analyzed. The results showed that the method of drill bit precooling could reduce the drilling temperature. The drill bit starting temperature and the feed rate were more important parameters on the drilling temperature compared with rotational speed and cooling length of the drill bit. The quadratic regression model obtained from response surface experiments can predicted the drilling temperature correctly under the range of process parameters in this study. The optimal parameter combination is rotational speed = 1610 rpm, feed rate = 0.5 mm/s, the starting temperature of drill bit = 8°C, and the cooling length = 34.8 mm. The results provide an effective method to reduce thermal necrosis of bone cells in drilling.